Determinan Status Kerawanan Pangan Rumah Tangga di Nusa Tenggara Timur 2021 - Br Lumban Gaol, Marta Desna Fitria; Sukim, Sukim (Seminar Nasional Official Statistics, 2023)
Households food insecurity in the Province of East Nusa Tenggara (NTT) has an urgency to address. Although regionally the province of NTT has a food secure status in 2021, the prevalence of people experiencing food insecurity in that province is the highest nationally. This study aims to analyze the determinants of households food insecurity status in NTT Province in 2021. This study uses two levels of analysis units, namely the households level and the districts/cities level by applying the multilevel binary logistic regression method. The data used are raw data and publications from the Central Bureau of Statistics (BPS). Most households in NTT Province are food insecure. Determinants of households food insecurity status in NTT Province in 2021 are area of residence, gender of head of household (HH), age of HH, field of business of HH, number of household members, household poverty status, status of food aid recipients, sources of proper drinking water, and the number of shops and markets.